Staycation and Leisure Time Analysis during The Covid-19 Pandemic - Ilma, Rudhya Nurul; Muktiarni, Muktiarni; Mupita, Jonah (Jurnal Abdimas Kartika Wijayakusuma, 2021)
The many changes as a result of the Covid-19 pandemic make people need to adjust to new habits and most of these activities are carried out at home. This community service is in the form of providing understanding and advice regarding activities that can be done during the pandemic for children and to fill their leisure time to be more productive. Measurement of the effectiveness of this activity is done by asking questions before the activity (pretest) and after the activity (posttest) and then comparing the results. The object of the activity is elementary school VB class students. The results of the activity showed that before giving the material, many students knew the term staycation from the mass media but did not really understand the use of leisure time. After giving the material, many students began to understand the use of leisure time with more productive activities, such as reading. They also get used to literacy activities before starting online learning activities, so that they can increase students' reading interest and foster literacy habits.